(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes modern mechanisms for digital monitoring of the movement of goods in the customs territory in the processing regime, issues of automating the processes of tracking and controlling commodity flows. Also, the main indicators used to assess the effectiveness of customs control, including time consumption, control accuracy, digital surveillance systems and risk management indicators, are studied. The study substantiates the possibilities of increasing transparency, reducing the human factor and creating convenience for participants in foreign economic activity in the processing customs regime through the introduction of digital technologies.